Effects of Resistance Training With Constant, Inertial, and Combined Loads on Muscle Power and Strength Output - Đurić, Saša; Knezevic, Olivera M.; Sember, Vedrana; Cuk, Ivan; Nedeljkovic, Aleksandar; Pajek, Maja; Mirkov, Dragan M. (Frontiers in Physiology, 2021)
The aim of study was to investigate the resistance-specific gains in muscle power and strength (1RM) following the training of maximum bench-press throws (BPT) against constant, inertial, and combined resistance. Forty-eight male participants (age 20.5±2.0 years) were randomly assigned to the constant, inertial, combined resistance, or control group. Participants underwent 8 weeks of training of BPT against the loads that corresponded to the different effects of mass of 40 kg (⁓50% of 1RM). The gains in average and maximum power, and in 1RM were significant in all experimental (P<0.01), but not in control-group (P>0.1). Relative gains in the average (26.3±9.8%) and maximum power (25.2±9.8%) were larger than in 1RM (mean 7.2±6.9%; both P<0.001). The gains in average (F4, 66=6.0; P<0.01) and maximum power (F4, 66=4.7; P<0.01) were higher when tested against the training-specific resistance than when tested against the remaining 2 resistance types. Differences in 1RM among experimental groups were not significant (P =0.092). The most important and a rather novel finding of the study is that the training against the weight and inertial resistance, and their combination results in resistance-specific gains in muscle power, although the overall gains muscle strength and power remain comparable across the training protocols.